ASME 2012 Summer Bioengineering Conference, Parts a and B 2012
DOI: 10.1115/sbc2012-80085
|View full text |Cite
|
Sign up to set email alerts
|

Regional Biomechanical and Microstructural Alterations of the Ovine Main Pulmonary Artery During Postnatal Growth

Abstract: It has been estimated that worldwide 600,000 babies are born annually with significant congenital heart disease (1). Congenital heart and related vascular defects cause increased flow and pulmonary pressure leading to unfavorable vascular remodeling that results in pulmonary arterial hypertension (1). Developing tissue engineered replacements that mimic the growth and remodeling behavior of native tissue is the optimal approach in treatment of congenital arterial anomalies. The understanding of the underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…As observed in our geometric studies [18,19], the focal changes in the medial region aie likely due to the impingement of relatively stiff ascending aorta on the growing PA. As observed in our geometric studies [18,19], the focal changes in the medial region aie likely due to the impingement of relatively stiff ascending aorta on the growing PA.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…As observed in our geometric studies [18,19], the focal changes in the medial region aie likely due to the impingement of relatively stiff ascending aorta on the growing PA. As observed in our geometric studies [18,19], the focal changes in the medial region aie likely due to the impingement of relatively stiff ascending aorta on the growing PA.…”
Section: Discussionsupporting
confidence: 72%
“…As observed in our geometric studies [18,19], the focal changes observed in the medial region are likely due to the impingement of relatively stiff ascending aorta on the growing PA. This effect is likely more pronounced since these two great vessels are held together within a connective tissue sheath (J. E. Mayer, Jr., private communication).…”
Section: Overall Findingssupporting
confidence: 75%
See 1 more Smart Citation
“…In their work, collagen fibre orientation was inferred from histological images, and probability functions describing collagen recruitment were postulated from the literature and from a qualitative observation of collagen waviness across the wall thickness. Fata et al 11,12 chose anisotropic SEFs for modelling both collagen and elastin and used multi-photon fluorescence of the ovine pulmonary artery wall tissue subjected to biaxial testing to determine collagen and elastin orientation distributions. Moreover, the waviness of the adventitial collagen was used to define a probabilistic recruitment function describing its delayed response.…”
Section: Introductionmentioning
confidence: 99%